On being human as praxis. - Wynter, Sylvia (Durham : Duke University Press, 2015)
McKittrick, Katherine ; Fanon, Frantz ; W.E.B. Dubois ; Césaire, Aimé
black studies, black diaspora, ras, ecology, filosofie, publieke ruimte, migratiepolitiek
boek
Keywords: Wynter, Sylvia